AVALIAÇÃO DO EFEITO NEUROPROTETOR IN VITRO DO EXTRATO DE AÇAÍ LIVRE E NANOESTRUTURADO EM MICRÓGLIAS E EM CÉLULAS NEURONAIS-LIKE EXPOSTAS A ROTENONA DE FORMA ISOLADA OU COADJUVANTE AO FÁRMACO RISPERIDONA - Fraga, Alessandra Soares Ayres (2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder. There is scientific evidence that indicates that accumulated amyloid beta peptide (Aβ), together with neurofibrillary tangles and TAU proteins, can initiate the development of neurodegeneration, neuroinflammation, and oxidative stress. Studies have demonstrated the neuroprotective effect of açaí extract, but without confirming that it can act as an adjuvant to any of the commercial drugs used for people with AD, such as risperidone, for example. Additionally, there are still no studies that perform a comparative analysis between the effects of free açaí extract and that present in a nanocarrier regarding its neuroprotective and modulatory properties of mitochondrial dysfunction. The aim of this study was to evaluate the in vitro neuroprotective effect of free and nanostructured açaí extract on microglia and neuronal-like cells exposed to rotenone alone or as an adjuvant to the drug risperidone. For this, the first stage of this work included the induction of mitochondrial dysfunction in complex I in microglial cells using rotenone. These cells were then treated with free açaí extract, risperidone or a combination of açaí extract and risperidone for 24 hours. The second stage of the study involved the production of a liposome containing açaí extract. Neuronal-like cells were induced to mitochondrial dysfunction and treated with the free or nanostructured extract for 24 hours. After treatments and incubation periods, different colorimetric, fluorimetric and microscopic tests were conducted. Statistical analysis was performed using GraphPad Prism software via one-way ANOVA, followed by Tukey's post hoc test. It was observed that açaí extract alone was able to restore cellular homeostasis in microglia with mitochondrial dysfunction. However, risperidone was not able to reverse the effects of rotenone neuron induction in all conditions tested. On the other hand, the association between açaí extract and risperidone demonstrated to induce an effect similar to that found for the extract per se. This suggests that açaí extract can be used as an adjuvant to the drug in individuals with neurodegenerative diseases. Regarding the production of a nanocarrier containing açaí extract, it can be said that it was possible to produce liposomal vesicles with physicochemical characteristics consistent with nanoscale materials. The nanocarrier containing açaí extract acted more effectively than the free extract in restoring normal cellular conditions in neuronal-like cells with induced mitochondrial dysfunction. It is believed that this profile is due precisely to the properties guaranteed by the nanostructure, thus potentially enhancing the effects and properties of the açaí extract. It is possible to suggest that free açaí extract can reverse mitochondrial dysfunction in complex I in microglia and that this effect is maintained even when the natural product is in association with the drug risperidone. Additionally, it was possible to observe that the effects of the nanostructured extract seem to surpass the benefits of the free extract in SH-SY5Y cells.